BIM content development : standards, strategies, and best practices - Weygant, Robert S., 1973- (Hoboken, N.J. : Wiley, 2011)
"From the cutting-edge of technology comes this book on Building Information Modeling (BIM), the newest technology in the AEC industry that allows the professional to create 3D models of a building that includes much more data than a traditional 2D CAD file. Developing BIM Content explains the type of information that can go into a BIM model from a vendor-neutral perspective and explores different methods for organizing content. For anyone interested in creating feature-rich BIM object and models that work on any platform, this is a must-have reference"--
"Provides an overview of the different industry standards currently being used (CSI's Masterformat, Uniformat, and Omniclass; Industry Foundation Classes) and how one can leverage them when creating objects and models Walks through what the different types of information are (parameters, attributes, constraints, and conditions) and how they inter-relate How to use this information to create and implement a data management strategy for your objects and models. The strategies and best practices outlined in this book are vendor-neutral; they can be used by any professional, regardless of the software platform in use"--
Includes index.
Keywords: Building information modeling; ARCHITECTURE / General